1984
DOI: 10.1080/02571862.1984.10634120
|View full text |Cite
|
Sign up to set email alerts
|

Screening for DIMBOA (benzoxazinone) concentration among South African inbred maize lines and sorghum cultivars

Abstract: Twenty-seven popular South African inbred maize lines, four commercial maize cultivars, two sweet corn cultivars and two grain sorghum cultivars were screened by means of a rapid, semi-quantitative method to determine DIMBOA concentration_ Significant differences were found between inbred lines. Sweet corn cultivars exhibited a relatively high concentration of DIM BOA, while grain sorghum contained a very low concentration. Although differences in concentration between plants cultivated from different seed siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Benzoxazinones are also known to catalyze the hydrolysis of the organophosphate pesticide diazinon (Ioannou et al, 1980), and have been found in several grasses, for example, Sorghum spp. (Malan et al, 1984), Triticum spp., including ancient wheats (Niemeyer, 1988a, 1988b), and Zea spp., including the Mexican variety teosinte (Chang and Brewbaker, 1975), and even in a few dicot families, for example, Acanthaceae and Scrophulariaceae (Friebe et al, 1998). It has been shown that the degradation of atrazine to hydroxyatrazine was promoted in the rhizosphere of corn (Alvey and Crowley, 1996).…”
mentioning
confidence: 99%
“…Benzoxazinones are also known to catalyze the hydrolysis of the organophosphate pesticide diazinon (Ioannou et al, 1980), and have been found in several grasses, for example, Sorghum spp. (Malan et al, 1984), Triticum spp., including ancient wheats (Niemeyer, 1988a, 1988b), and Zea spp., including the Mexican variety teosinte (Chang and Brewbaker, 1975), and even in a few dicot families, for example, Acanthaceae and Scrophulariaceae (Friebe et al, 1998). It has been shown that the degradation of atrazine to hydroxyatrazine was promoted in the rhizosphere of corn (Alvey and Crowley, 1996).…”
mentioning
confidence: 99%
“…Hordeum lecheri, have been found to produce benzoxazinoids (Grün et al, 2005). There have also been some reports of benzoxazinoid production in sorghum (Malan et al, 1984;Niemeyer, 1988). Several other less well-known species in the Poaceae (e.g.…”
Section: Distribution Of Benzoxazinones In Poaceaementioning
confidence: 99%
“…Malan, Visser & Vande Venter (1984) screened a number of inbred maize lines for OIMBDA content and found significant differences between inbred lines. Significant differences among 33 maize inbreds of which 15 were also screened for DIMBDA content (Malan et al, 1984), were found for tolerance to atrazine with leaf dry mass response as indicator of tolerance (Le Court de Billot, Fourie & Nel, 1986). The objective of this study was to determine whether a significant correlation existed between the OIMBDA content and atrazine tolerance in maize inbreds, in order to show the importance of atrazine hydroxylation in pre-emergence atrazine-treated maize plants.…”
Section: Relationship Between Dimboa Content and Atrazine Tolerance Inmentioning
confidence: 99%
“…Screening of maize inbreds for OIMBDA content was done using the FeCh test with colorimetric quantification (Malan et al, 1984) while atrazine tolerance was determined in a glasshouse using a sand culture technique and leaf dry mass response as indicator of tolerance (Le Court de Billot et al, 1986). Maize inbreds common to the two independant studies are listed in Table 1 and the data were subjected to standard correlation and regression (linear and polynomial) analysis.…”
Section: Relationship Between Dimboa Content and Atrazine Tolerance Inmentioning
confidence: 99%